Antigiardial Activity of Novel Guanidine Compounds. (29th September 2022) - Stevens, Andrew J.; Abraham, Rebecca; Young, Kelly A.; Russell, Cecilia C.; McCluskey, Siobhann N.; Baker, Jennifer R.; Rusdi, Bertha; Page, Stephen W.; O'Handley, Ryan; O'Dea, Mark; Abraham, Sam; McCluskey, Adam
Abstract: From four focused compound libraries based on the known anticoccidial agent robenidine, 44 compounds total were synthesised and screened for antigiardial activity. All active compounds were counter‐screened for antibiotic and cytotoxic action. Of the analogues examined, 21 displayed IC50 <5 μM, seven with IC50 <1.0 μM. Most active were 2, 2′‐ bis [4‐(trifluoromethoxy)phenyl]methylenecarbonimidic dihydrazide hydrochloride (30 ), 2, 2′‐ bis [4‐(trifluoromethylsulfanyl)phenyl]methylenecarbonimidic dihydrazide hydrochloride (32 ), and 2, 2′‐bis[(2‐bromo‐4, 5‐dimethoxyphenyl)methylene]carbonimidic dihydrazide hydrochloride (41 ) with IC50 =0.2 μM. The maximal observed activity was a 5 h IC50 value of 0.2 μM for 41 . The clinically used metronidazole was inactive at this timepoint at a concentration of 25 μM. Robenidine off‐target effects at bacteria and cell line toxicity were removed. Analogue 41 was well tolerated in mice treated orally (100 mg/kg). Following 5 h treatment with 41, no Giardia regrowth was noted after 48 h. Abstract : Rapid and complete killing of Giardia trophozoites: From four focused compound libraries based on the known anticoccidial agent robenidine, 44 compounds were synthesised and screened for antigiardial activity. All active compounds were counter‐screened for antibiotic and cytotoxic action. Of the analogues examined, 21 displayed IC50 values less than 5 μM, seven with IC50 values less than 1.0 μM.